Incidence, distribution and first identification of citrus tristeza virus by RTPCR in citrus orchards in southWestern Nigeria - Adediji, A.O.; Atiri, G.I.; Kumar, P. Lava (International Society for Horticultural Science, 2015)
In order to ascertain the presence, incidence, and distribution of Citrus tristeza virus (CTV), extensive surveys were conducted in citrus growing areas of south-western Nigeria during 2011-12. A total of 565 citrus trees were sampled in three states. Leaf samples were collected and symptom intensity of the trees was recorded. Symptoms observed included stem pitting, stunting, vein clearing and leaf curling. Nucleic acid extracts from leaves were used to detect CTV by RT-PCR using primers PIN1 and PIN2 directed to the conserved 3’ untranslated region. Results show the presence of CTV in the three states surveyed while symptom severity differed from one location to another. Disease incidence varied from 85.2% in Oyo State to 48.4% in Ogun State. Citrus trees were infected regardless of scionrootstock combinations and the virus was detected in sweet orange (87.0%), tangerine (77.6%), grapefruit (73.8%) and lemon (69.5%). This is the first report of molecular detection of CTV in Nigeria.In order to ascertain the presence, incidence, and distribution of Citrus tristeza virus (CTV), extensive surveys were conducted in citrus growing areas of south-western Nigeria during 2011-12. A total of 565 citrus trees were sampled in three states. Leaf samples were collected and symptom intensity of the trees was recorded. Symptoms observed included stem pitting, stunting, vein clearing and leaf curling. Nucleic acid extracts from leaves were used to detect CTV by RT-PCR using primers PIN1 and PIN2 directed to the conserved 3’ untranslated region. Results show the presence of CTV in the three states surveyed while symptom severity differed from one location to another. Disease incidence varied from 85.2% in Oyo State to 48.4% in Ogun State. Citrus trees were infected regardless of scionrootstock combinations and the virus was detected in sweet orange (87.0%), tangerine (77.6%), grapefruit (73.8%) and lemon (69.5%). This is the first report of molecular detection of CTV in Nigeria.